PENGARUH PARTISIPASI GURU DALAM PENGAMBILAN KEPUTUSAN DAN IMPLEMENTASI PENGAWAS TERHADAP KINERJA GURU - Hasan Muthi (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2019)
This study aims to obtain information on the performance of MTs teachers in the KKM MTsN Cimerak: (1) teacher participation in making decisions on teacher performance. (2) the effect of teacher participation in the implementation of supervision on teacher performance. (3) Is there a relationship between teacher participation in decision making and implementation of supervision on teacher performance. The research method uses descriptive-correlational method. Data collection by observation and questionnaire to 30 respondents. The results of the study concluded: (1) The results of testing using the Spearman's Rho Correlation Test between Variable X1 (Teacher Participation in Decision Making) with Y Variable (Teacher Performance), obtained the Spearmen's Rho Correlation Coefficient of 0.685, means a moderate correlation. (2) The test results using Pearson Product Moment Correlation Test between Variable X2 (Teacher Participation in Supervision Implementation) with Y Variable (Teacher Performance), obtained Pearson correlation coefficient (r) of 0.804, highly correlated. (3) The results of testing using the multiple correlation test for Variables X1 and X2 with Variable Y, the double correlation coefficient (r) is 0.848, which means high correlation. Based on the test results the significance level is 0,000, which means far below 0.05. Thus, it can be concluded that there is a positive influence between teacher participation in joint decision making and teacher participation in the implementation of supervision of performance improvement in MTs throughout the MTsN Cimerak KKM.